GABAergic synaptic transmission regulates calcium influx during spike-timing dependent plasticity - Balena, Trevor; Acton, Brooke A.; Woodin, Melanie A. (Frontiers in Synaptic Neuroscience, 2010)
Coincident pre- and postsynaptic activity of hippocampal neurons alters the strength of gamma-aminobutyric acid (GABAA)-mediated inhibition through a Ca2+-dependent regulation of cation-chloride cotransporters. This long-term synaptic modulation is termed GABAergic spike-timing dependent plasticity (STDP). In the present study, we examined whether the properties of the GABAergic synapses themselves modulate the required postsynaptic Ca2+ influx during GABAergic STDP induction. To do this we first identified GABAergic synapses between cultured hippocampal neurons based on their relatively long decay time constants and their reversal potentials which lay close to the resting membrane potential. GABAergic STDP was then induced by coincidentally (± 1 ms) firing the pre- and postsynaptic neurons at 5 Hz for 30 seconds, while postsynaptic Ca2+ was imaged with the Ca2+-sensitive fluorescent dye Fluo4-AM. In all cases, the induction of GABAergic STDP increased postsynaptic Ca2+ above resting levels. We further found that the magnitude of this increase correlated with the amplitude and polarity of the GABAergic postsynaptic current (GPSC); hyperpolarizing GPSCs reduced the Ca2+ influx in comparison to both depolarizing GPSCs, and postsynaptic neurons spiked alone. This relationship was influenced by both the driving force for Cl- and GABAA conductance (which had positive correlations with the Ca2+ influx). The spike-timing order during STDP induction did not influence the correlation between GPSC amplitude and Ca2+ influx, which is likely accounted for by the symmetrical GABAergic STDP window.